Do municipal mergers reduce costs? Evidence from a German federal state. - Blesse, Sebastian; Baskaran, Thushyanthan (My University, 2014)
The authors study the fiscal consequences of municipal mergers by making use of a largescale merger reform in the German federal state of Brandenburg. In addition to being the first evaluation of an East-German merger reform, this study contributes to the literature by exploring the fiscal consequences of both compulsory and (semi-) voluntary municipal mergers within the same institutional setting. Using a difference-in-difference design with municipality-level panel data over 1998-2005, the authors find substantial and immediate reductions in total, administrative, and current expenditures after compulsory mergers. Voluntary mergers, on the other hand, have smaller and less robust effects.
Keywords: Haushaltswesen; Kostenanalyse; Finanzwesen; Gebietsreform; Gemeindefinanzen; Studie; Stadtgebiet; Zusammenschluss